Computerized cognitive training using virtual reality on everyday life activities for patients recovering from stroke - Oliveira, Jorge (2022)
Recent studies argue that the use of virtual reality tasks depicting activities daily living may be an effective means for cognitive rehabilitation. The aim of this study was to test an ecologically oriented approach in virtual reality resembling the demands of everyday life activities for cognitive rehabilitation following stroke. The sample comprised 30 sub-acute stroke patients recovering from stroke in a rehabilitation hospital. They were assessed in a single-arm pre-post intervention study on global cognition, executive functions, memory and attention abilities. The intervention consisted of virtual reality in a multidomain cognitive training approach depicting everyday life tasks (preparing food, choosing clothes, shopping, etc.). Improvements were found in the assessed cognitive domains at 6 to 10 post-treatment sessions. In-depth analysis through reliable change scores has suggested larger treatment effects on global cognition. Overall results suggest that the use of virtual reality-based exercises on everyday life activities may be a useful cognitive rehabilitation approach to provide short-term gains in cognition following stroke.